Notes on distributions for Argentinean Pentatomidae (Heteroptera: Pentatomoidea), with new records in the country - Dellapé, Gimena (2015)
In this contribution, we present new distributional records from Argentina of 63 pentatomid species; three genera (. Caonabo, Cromata and Taurocerus) and 14 species (. Marmessulus brasiliensis, Podisus crassimargo, Cromata ornata, Acledra haematopa, Caonabo pseudocylax, Dichelops avilapiresi, Euschistus cribarius, E. paranticus, Mormidea maculata, Rio indistinctus, Banasa lanceolata, B. nigrifrons, Pallantia macunaima, and Taurocerus edessoides) are reported for the first time from Argentina; also we provided 81 new province records of another 49 species.